2018
DOI: 10.4236/ojbm.2018.64062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mobile Credit on Operational Efficiency in Commercial Banks in Kenya

Abstract: This study sought to establish the effect of mobile credit on operational efficiency in commercial banks in Kenya. The study utilized primary as well as secondary data on access to mobile credit and its effects on the performance of the organization. A questionnaire was the primary data collection tool and composed of open ended and closed ended questions. Data collected was analyzed using multiple linear regression analysis at a 95% confidence interval. Analyzed data was presented using tables and figures for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Research carried out by Orina (2020) with the purpose of assessing the effect that mobile banking has on the operational efficiency of commercial banks. The study was conducted using a descriptive research methodology, and it employed 41 different commercial banks as its primary subjects.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research carried out by Orina (2020) with the purpose of assessing the effect that mobile banking has on the operational efficiency of commercial banks. The study was conducted using a descriptive research methodology, and it employed 41 different commercial banks as its primary subjects.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…The study also found that default patterns and risk profiles significantly impacted commercial banks' overall financial performance in a negative way. Research carried out by Orina (2020) with the purpose of assessing the effect that mobile banking has on the operational efficiency of commercial banks and established that mobile based loan management has significant influence on the operational efficiency of commercial banks. However, Kariuki (2019) aimed to determine the impact that the use of technology has on the overall performance of Deposit Taking Saccos by using K-Unity Sacco as a case study.…”
Section: Source: Field Data (2023)mentioning
confidence: 99%
“…The empirical findings indicated that 65% of variation in operational efficiency of banks was explained to the number of annual transactions and the number of accounts. Kinyanzui, Kiriri and Achoki (2018) undertook a research to investigate on the impact of mobile credit on the operational efficiency of Kenyan banks using a mix of both primary and secondary data on credit accessibility and its effect on enterprises performance. A questionnaire with a mix of open ended and closed ended questions was used in collection of data.…”
Section: Mobile Lendingmentioning
confidence: 99%
“…Adhitya and Sembel (2020) found that technology adoption strengthens bank's financial performance and increase bank's competitiveness. Kinyanzui et al (2018) argued that acceptance of technology is one of the major strategies of bank to enhance operational efficiency. Technological innovation creates competitive advantage (Hobe & Alas, 2016) by improving bank's performance, attracting new customers and provides financial products and services that meet needs and wants of customers.…”
Section: Theoretical Review On Technology Innovation and Bank Perform...mentioning
confidence: 99%
“…Hobe and Alas (2016), Abualloush et al (2017), Kołodziej (2017) and Kinyanzui et al (2018) argued that technology innovation can enhance operational efficiency of a firm, however, there is a scarcity of banking studies that demonstrate how electronic payments can improve a bank's operational efficiency. Based on the research gap, we expect that electronic payments could enhance a bank's operating income.…”
Section: Hypotheses Developmentmentioning
confidence: 99%